Alternative payment models: can (should) trauma care be bundled?. Issue 1 (6th June 2018) - Kerwin, Andrew James; Mercel, Alexandra; Skarupa, David J; Tepas, Joseph J; Ra, Jin H; Ebler, David; Hsu, Albert; Shiber, Joseph; Crandall, Marie L
Abstract : Background: Recent legislation repealing the Sustainable Growth Rate mandates gradual replacement of fee for service with alternative payment models (APMs), which will include service bundling. We analyzed the 2 years' experience at our state-designated level I trauma center to determine the feasibility of such an approach for trauma care. Methods: De-identified data from all injured patients treated by the trauma service during 2014 and 2015 were reviewed to determine individual patient injury profiles. Using these injury profiles we created the 'trauma bundle' by concatenating the highest Abbreviated Injury Scale score for each of the six body regions to produce a single 'signature' of injury by region for every patient. These trauma bundles were analyzed by frequency over 2 years and by each year. The impacts of physiology and resource consumption were evaluated by determination of the correlation of the mean and SD of calculated survival probability (Ps) and intensive care unit length of stay (ICU LOS) for each profile group occurring more than 12 times in 2 years. Results: The 5813 patients treated over 2 years produced 858 distinct injury profiles, only 8% (71) of which occurred more than 12 times in 2 years. Comparison of 2014 and 2015 profiles demonstrated high frequency variation among profiles between the 2 years. Analysis of injury patterns occurring >12 times in 2 years demonstrated an inverse correlation between the mean and SD for Ps (R 2 =0.68) and a direct correlation for ICU LOS (R 2 =0.84). Discussion: These data indicate that the disease of injury is too inconsistent a mix of injury pattern and physiologic response to be predictably bundled for an APM. The inverse correlation of increasing SD with increasing ICU LOS and decreasing Ps suggests an opportunity for measurable process improvement. Level of evidence: Economic and value-based evaluations, level IV. Study type: Economic/decision.